1997
DOI: 10.1016/s0014-5793(97)01270-2
|View full text |Cite
|
Sign up to set email alerts
|

The 5′‐untranslated region of the human muscle acylphosphatase mRNA has an inhibitory effect on protein expression

Abstract: The cDNA of the human muscle type acylphosphatase was isolated and characterized. The mRNA presents a very long 5'-untranslated region, covering the first half of the molecule: 175 bases of this part were cloned and prediction of the possible secondary structure showed that a very stable stem-loop structure could be formed in that region. Moreover, an additional AUG triplet was found upstream of the start codon of the protein, defining an open reading frame of 60 codons which overlapped that of acylphosphatase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…Moreover, it can be observed that nearly half of the single mRNA transcript coding for AcPDro is unusually covered by the 5'-UTR. A very similar situation has been found for the human MT-AcP mRNA where it was also evidenced that the 5'-UTR plays a role in the stability of the mRNA molecule [26].…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, it can be observed that nearly half of the single mRNA transcript coding for AcPDro is unusually covered by the 5'-UTR. A very similar situation has been found for the human MT-AcP mRNA where it was also evidenced that the 5'-UTR plays a role in the stability of the mRNA molecule [26].…”
Section: Discussionsupporting
confidence: 78%
“…Surprisingly, the N41Q-AcP mutant, a protein that has lost most of its in vitro acylphosphatase activity on benzoyl-phosphate [18] and ATP [23], behaves exactly as the wild-type enzyme for what cell survival is concerned, thus suggesting that the well characterized in vitro acylphosphatase activity of this protein is not necessary for AcP-induced cell death. The results that we have exposed in this work are very interesting in the light of an important observation of Fiaschi et al [13] on the regulation of AcP expression mediated by the 5Ј-UTR of its mRNA. The primary target for translational control is at the initiation step, and control of translational initiation on individual mRNA is determined primarily by the structural properties of the mRNA, particularly the 5Ј-UTR [24].…”
Section: Flow Cytometry and Time-lapse Analysis Of Acp-transfected Cellssupporting
confidence: 55%
“…The most important 5Ј-UTR features that control mRNA translation are its secondary structures, the presence of additional initiation AUG codons and of an upstream open reading frame. Fiaschi et al [13] have found that the 5Ј-UTR of AcP has an inhibitory effect on protein expression because possess both an upstream AUG and a very stable stem-loop structure. Interestingly, only less than 10% of the vertebrate mRNAs contains initiation codons upstream the major open reading frame [25].…”
Section: Flow Cytometry and Time-lapse Analysis Of Acp-transfected Cellsmentioning
confidence: 99%
See 2 more Smart Citations